Digital workflow for a space maintainer in a pediatric patient: a case report - Pérez-Flores, Antonieta (2025)
This case report describes the use of digital technology in pediatric dentistry to fabricate a space maintainer for a 6-year-old patient with dental anxiety and fear related to previous traumatic experiences. An intraoral scanner and computer-aided design software were used to generate a three-dimensional digital model of the dental arch, on which the space maintainer was designed and fabricated. The device was made from polymethyl methacrylate using a subtractive dry-milling process. Incorporating a digital workflow into clinical care may provide a less invasive and more comfortable alternative for managing children with dental anxiety and fear of dental treatment.